The Influence of Tax Audits and Tax Collections on the Disbursement of Tax Arrears in the Southern Part of Sumatra, Indonesia - Kusumawaty, Mia; Kurniawan, M. Orba; Ramadhan, Arif Syahrul (Manunggal Halim Jaya, 2025)
This study was conducted to determine the effect of tax audits and collection on tax arrears' disbursement. This study uses an associative research type. The research was conducted in the Pratama Ilir Barat Tax Service Office, Palembang City, Indonesia, involving approximately 100 respondents. The sample used was Probability Sampling, namely, simple random sampling. The variables used in this study are Tax Audit and Tax Collection. The primary data used in this study is primary data. Data collection techniques were carried out using questionnaires. Hypothesis testing shows that tax audits and collections significantly affect the disbursement of tax arrears. Overall, a good relationship between tax officers and taxpayers, coupled with an efficient tax audit process and information technology support, can significantly affect the disbursement of tax arrears by accelerating payments and reducing the possibility of delays. The final results show that tax audits affect the disbursement of tax arrears. The better and more tax collection, both by warning and coercion by the tax authorities, results in higher and greater disbursement of tax arrears. Furthermore, the disbursement of tax arrears will certainly increase tax revenues. The study found that law enforcement against the settlement of tax arrears has been carried out seriously by the authorities, in this case, the local Regional Tax and Retribution Agency.